Do individual programme effects exceed the costs? Norwegian evidence on long run effects of labour market training - Oddbjørn Raaum; Hege Torp; Tao Zhang (University of Oslo, Department of Economics, 2002)
Individual long run effects of a labour market training programme targeted at unemployed adults are evaluated by comparing mean post-training earnings for matched samples of participants and non-participants. Average training effects on the trained are positive and persistent over the posttraining period of 5 years. Participants without recent work experience, prior to the training, gain less. For participants with recent work experience the present value of the 5 years accumulated earnings effect exceeds the direct costs of the training.
Keywords: C14; J64; J68; 330; Training unemployed; causal effects; matching estimators; accumulated long run effects; Arbeitslosigkeit; Schätzung; Norwegen; Berufliche Integration; Matching